PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, LEVERAGE, DAN KUALITAS AUDITOR TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2015-2016) - : Debi Putri Kenanga, 14.05.52.0026; Poerwati, Rr. Tjahjaning (Students Journal of Accounting and Banking, 2018)
The purpose of this research is the discover and analyze the effect of the managerial ownership, institusional ownership, leverage, and auditor quality to the earnings management. The research is an empirical study. The data source is secondary data obtained by using documentation technique. This study use documentary method from Indonesia Capital Market Directory (ICMD) and annual reports of manufacture companies. Samples were taken by using purposive sampling technique. Samples were 70 companies from 155 companies listed in Indonesia Stock Exchange in 2015-2016, so that the research data was analyzed totaled 140. To analyze the hypothesis used logistic regression analysis. The research shows that the variable of institusional ownership and leverage do not any have significant influence to the earnings management, meanwhile the managerial ownership and auditor quality have significant influence to the earnings management.Keywords: Earnings Management, Managerial Ownership, Institusional Ownership, Leverage, and Auditor Quality.